Guru Sahabat Siswa: Program Kesehatan Reproduksi bagi Guru - Rieka Esti Saraswati; Ira Paramastri (Faculty of Psychology, Universitas Gadjah Mada, 2013)
The issue of reproductive health is increasing year by year. Proper understanding of reproductive healt his absolutely necessary for students at school. Teacher is one of the important part in learning process, so teachers must have an understanding of reproductive healt has well as sufficient skills to deliver it properly to the students. The purpose of this study is to know the effectiveness of the